United in Times of War: Reading Mickey in 1940-1944 France - Eva Van De Wiele (Strenae)
Comics have built and maintained relationships with their readers over time, leading to what Martin Barker has called a “contract”. Roger Sabin, for instance, has demonstrated how the Ally Sloper’s Half Holliday papers of the nineteenth century fostered a sense of friendship with readers, who felt their opinions were being heard. Similarly, children’s magazines used reader interaction as an affective tool for marketing purposes and for political indoctrination. One prominent example is the French children’s weekly, Le journal de Mickey, which from 1934 created a community through letters, competitions, and clubs. This article examines the rarely studied reader participation sections of Le journal de Mickey from 1940 to 1944, produced in Marseille. Reflecting implied rather than actual readers, these sections reveal how, during World War II, children were both provided with consolation for the war and distraction from it, and mobilized and engaged in the war effort. I investigate the impact of Club Mickey’s promotion of social cohesion through children’s activities during this period. Combining qualitative close readings with a quantitative overview, the article analyses changes in the magazine’s interactive sections from 1940 to 1944. It highlights the shift from American to domestic content, the fine balance between national propaganda and affective support of readers, and the roles and responsibilities of children in war. This research fills a gap in the study of children’s magazines during World War II, extending methodologies from studies by Stéphane Audoin-Rouzeau and Manon Pignot on the First World War to understand the effects of the Second World War on French child readers.